African wild dogs: Genetic viability of translocated populations across South Africa. (June 2019) - Tensen, Laura; van Vuuren, Bettine Jansen; du Plessis, Cole; Marneweck, David G.
Abstract: South Africa holds a viable population of the endangered African wild dog ( Lycaon pictus ), with almost 500 individuals divided into (1) an unmanaged population in the Kruger National Park (KNP), (2) a free-roaming population, and (3) a managed metapopulation (MTP) that originated from reintroductions. Because metapopulation reserves are geographically isolated, translocations are ongoing to mimic natural dispersal. During this study, we questioned whether the metapopulation management plan for wild dogs has been successful at maintaining healthy levels of genetic diversity and avoiding inbreeding in packs. We evaluated whether the current approach is effective for long-term population viability and assessed whether population admixture occurs between the three populations. To achieve this, we amplified 20 microsatellite loci for genetic analysis. We found high levels of genetic variation, likely resulting from translocations and artificial pack formation. Results showed that in the absence of any management intervention, the MTP would lose 48% of its heterozygosity over a 100-year trajectory, and KNP 12% heterozygosity. Under the current management scenario, the MTP will maintain 95% of its heterozygosity. We found genetic evidence that limited recent dispersal occurs between the MTP and KNP (FST  = 0.06). In conclusion, the metapopulation management plan can be considered successful based on the achieved population growth and preservation of genetic diversity. Our study highlights that genetic data form a critical part of conservation management, and that translocations can be a vital tool to restore genetic variability of species. Highlights: The metapopulation plan for African wild dogs successfully achieved population growth. Without intervention, the metapopulation would lose 48% of its genetic diversity. Genetic differentiation is apparent, although population admixture occurs. Translocations between reserves remain essential for future population viability. Genetic data form a critical part of conservation management.